2008
DOI: 10.1007/s11095-008-9579-2
|View full text |Cite
|
Sign up to set email alerts
|

Different Curcuminoids Inhibit T-Lymphocyte Proliferation Independently of Their Radical Scavenging Activities

Abstract: Curcuminoid-induced inhibition of OKT3-induced PBMC proliferation depends on the number of carbon atoms and double bonds of the 1,6-heptadiene-3,5-dione structure as well as on the phenolic ring substitutes of the curcuminoids but is not correlated to their respective radical scavenging activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…The reduced metabolites, tetra-, hexa-, and octahydrocurcumin, have either greatly decreased or different biological activity compared with curcumin (43)(44)(45). In a few instances the biological activities of the putative degradation products vanillin, ferulic acid, and feruloylmethane were investigated, and these were also found to be only weakly active, at best, when compared with the same effects of curcumin (10,12,46,47). There is the possibility, however, that the quinone methide intermediate or the bicyclopentadione product are biologically active and responsible for some of the activities of curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced metabolites, tetra-, hexa-, and octahydrocurcumin, have either greatly decreased or different biological activity compared with curcumin (43)(44)(45). In a few instances the biological activities of the putative degradation products vanillin, ferulic acid, and feruloylmethane were investigated, and these were also found to be only weakly active, at best, when compared with the same effects of curcumin (10,12,46,47). There is the possibility, however, that the quinone methide intermediate or the bicyclopentadione product are biologically active and responsible for some of the activities of curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the active sites of curcumin and tetrahydrocurcumin related to their antioxidative activity are composed of hydroxy and carbonyl groups located in the centers of their chemical structures (15). Furthermore, it has been reported that curcuminoids inhibit T-lymphocyte proliferation independently of their radical scavenging activity; the inhibitory effects were dependent on the number of carbon atoms and doubles of the 1,6-heptadiene-3,5-dione structure as well as on the phenolic ring substitutes of the curcuminoids, and were not correlated to their respective radical scavenging activity (25). Curcumin, tetrahydrocurcumin and monoacetylcurcumin all include hydroxy plus carbonyl groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell numbers and viability were then estimated on the basis of trypan blue exclusion by counting in Vi-Cell™ XR cell viability analyzer (Beckman Coulter Inc., Fullerton, CA). PBMC proliferation was determined by the standard 3 H-thymidine incorporation assay (22,23). Briefly, cells were treated in 96-well plates (10 5 cells/well) with either ethanol and/or DMSO vehicle (control) or CUR, CA and SIL, alone and in combination, in the presence of 35 μg/ml phytohemagglutinin (PHA), for 54 h. Negative control cells were incubated with vehicle in the absence of PHA.…”
Section: Methodsmentioning
confidence: 99%